2019
DOI: 10.1016/j.freeradbiomed.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-oxidant properties of near-infrared (NIR) light responsive carbon nanoparticles

Abstract: Elemental carbon nanomaterials (ECNMs) are redox active agents that can be exploited to purposely modify the redox balance of cells. Both pro-or antioxidant properties have been reported. However, to the best of our knowledge, there are not comprehensive studies exploring both properties on the same material in view of a potential application in medicine. At the same time, the effect of the bulk structure on the pro/antioxidant properties is poorly known. Here, carbon nanoparticles (CNPs) derived by glucose wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 76 publications
4
55
0
Order By: Relevance
“…Obviously, the intensity of the peaks continuously increased when the mixture of NP IV and TEMP were irradiated under 808 nm laser, which represented the appearance of the adduct of TEMP‐ 1 O 2 , indicating the generation of singlet oxygen from the NPs IV. Furthermore, a very strong singlet peak was also observed in Figure B, which was assigned to carbon‐centered free radicals inside the NPs, consistent with the Raman spectra. Obviously, the intensity also increased along with the increase of the irradiation time.…”
Section: Figuresupporting
confidence: 79%
“…Obviously, the intensity of the peaks continuously increased when the mixture of NP IV and TEMP were irradiated under 808 nm laser, which represented the appearance of the adduct of TEMP‐ 1 O 2 , indicating the generation of singlet oxygen from the NPs IV. Furthermore, a very strong singlet peak was also observed in Figure B, which was assigned to carbon‐centered free radicals inside the NPs, consistent with the Raman spectra. Obviously, the intensity also increased along with the increase of the irradiation time.…”
Section: Figuresupporting
confidence: 79%
“…Carbon nanoparticles (CNPs) derived by glucose have been also reported to have pro- or anti-oxidant properties [106]. Kokalari and colleagues demonstrated that when irradiated with a near-infrared (NIR) laser, CNPs generate heat and singlet oxygen ( 1 O 2 ), which is useful for dual photothermal (PT)/photodynamic (PD) therapy in cancer treatment [107]. On the other hand, CNPs react with both oxidant (hydroxyl radicals) and antioxidant (glutathione) species when not photoactivated in a cell-free system.…”
Section: Polymeric Formulationsmentioning
confidence: 99%
“…CNPs were obtained by hydrothermal carbonization following a previously optimized protocol [18], without modifications. Briefly, 2 g of glucose were dissolved in 50 ml of ultrapure water and subsequently 15 mg of sodium polyacrylate were added.…”
Section: Synthesis and Sterilization Of Cnpsmentioning
confidence: 99%
“…One aliquot of the suspension was stored at 4 • C and used as a control for comparison with the sterilized sample in terms of hydrodynamic diameter, ζ-potential (using Zetasizer Nano, Malvern Instruments, Malvern, UK) and pH. Samples were also subjected to thermogravimetric analysis, as previously described [18], to detect changes in internal structure due to the high temperature during sterilization. Sterilization was further confirmed by the absence of bacterial contamination in the agar plate test based on a protocol developed by the European Nanomedicine Characterization Laboratory [24].…”
Section: Synthesis and Sterilization Of Cnpsmentioning
confidence: 99%
See 1 more Smart Citation